A review of evidence for pneumococcal vaccination in adults at increased risk of pneumococcal disease: risk group definitions and optimization of vaccination coverage in the United Kingdom - James Campling; Andrew Vyse; Hui-Hsuan Liu; Hannah Wright; Mary Slack; Ralf-Rene Reinert; Mark Drayson; Alex Richter; Dave Singh; Gavin Barlow; George Kassianos; Gillian Ellsbury (Taylor & Francis Group, 2023)
Introduction Pneumococcal disease (PD) significantly contributes to morbidity and mortality, carrying substantial economic and public health burden. This article is a targeted review of evidence for pneumococcal vaccination in the UK, the definitions of groups at particular risk of PD and vaccine effectiveness. Areas covered Relevant evidence focusing on UK data from surveillance systems, randomized controlled trials, observational studies and publicly available government documents is collated and reviewed. Selected global data are included where appropriate. Expert opinion National vaccination programs have reduced the incidence of vaccine-type PD, despite the rising prominence of non-vaccine serotypes in the UK. The introduction of higher-valency conjugate vaccines provides an opportunity to improve protection against PD for adults in risk groups. Several incentives are in place to encourage general practitioners to vaccinate risk groups, but uptake is low-suboptimal particularly among at-risk individuals. Wider awareness and understanding among the public and healthcare professionals may increase vaccination uptake and coverage. National strategies targeting organizational factors are urgently needed to achieve optimal access to vaccines. Finally, identifying new risk factors and approaches to risk assessment for PD are crucial to ensure those at risk of PD can benefit from pneumococcal vaccination.